EFISIENSI PROSEDUR PENGELUARAN KAS KECIL DI PT BPR HASAMITRA MAKASSAR - Syafrimansyah, Syafrimansyah; Firdaus , Ahmad; Wahab , Abdul (Universitas Lancang Kuning, 2024)
The management of petty cash within a company is a crucial aspect to support the smooth operation of daily activities. PT BPR Hasamitra Branch Daya Makassar implements petty cash disbursement procedures aimed at ensuring that small cash expenditures are conducted accurately and efficiently. This study employs a qualitative descriptive approach. Data were collected through direct observation, interviews with relevant employees, and documentation from PT BPR Hasamitra Branch Daya Makassar. Data analysis was conducted to evaluate the alignment of the petty cash disbursement procedures with existing theory. The results show that the petty cash disbursement procedures at PT BPR Hasamitra Branch Daya Makassar comply with the established theory and operational standards. The implemented procedures include the categorization of expense types, authorization of expenditures by superiors, and detailed recording of transactions. The proper implementation of petty cash disbursement procedures helps reduce the risk of fund misuse and ensures that funds are used for appropriate purposes. Additionally, supporting documents such as cash out receipts and requests for petty cash replenishment facilitate the audit and internal verification process. The petty cash disbursement procedures at PT BPR Hasamitra Branch Daya Makassar have been shown to be effective in supporting company operations and reducing the risk of fund misuse. The results of this study provide significant contributions to the company in managing petty cash more efficiently and effectively. Moreover, these findings can be used as a reference for other companies looking to improve their petty cash management. In a broader context, this study highlights the importance of good procedural implementation in petty cash management to support transparency and accountability in company operations